Strategi Mitigasi Risiko Terhadap Aset Keuangan dan Fisik Koperasi Melalui Penerapan Key Risk Indicators - Muhamad Nugraha; Nurul Aini (UII, 2022)
Assets are part of wealth owned by an industry and necessary to controlled, therefore loss risk can be identified and avoided, including occur at Cooperatives entity/sector. Cooperatives escalates their percomance not only depend on assets of members, but also require various efforts including outside business operations, so that it can be deliver financial and operational impact. Through the key risk indicator approach and cooperative performance analysis with measurement of growth and independence ratio, obtained 10 (ten) main risks and 15 key indicators to mitigated as preventive action by management of “Koperasi Pegawai Industri XYZ”. Moreover, mitigation strategies especially required at target of Key Risk Indicator aspect of Management and Organizations, People and Culture, and Operations & Systems. The other target are products, services and technology aspek, as supporting mitigation strategies necessary. Therefore, the expectation needed to management “Koperasi Pegawai Industri XYZ” conduct controlling risks of financial assets and physical assets, increasing continous growth and continous autonomy.